Inventory Information System Integration at CV. XYZ Web-Based - Dwi Iskandar; Andre Tantri Yanuar (International Journal of Computer and Information System (IJCIS), 2023)
A company that utilizes information technology optimally can survive in this global era, because by utilizing information technology companies can access information quickly, precisely and accurately and can provide effective and efficient services. Companies need technological assistance such as an application that can increase customer satisfaction. Service quality needs to get great attention from the company, because service quality has a direct relationship with the company's competitive ability and profit level. The research method used is a descriptive method that collects data systematically. This descriptive research method is supported by the Waterfall model software development method. The conclusions from this study include (1). Implementation of Inventory Information System Integration in CV. XYZ Web-based, (2). Information systems can carry out data input activities, data processing and data reports properly, (3). The information system provides database backup and database restore utilities